2017
DOI: 10.1108/lhs-10-2016-0047
|View full text |Cite
|
Sign up to set email alerts
|

Understanding critical care nurses’ autonomy in Jordan

Abstract: Purpose The aim of this study was to describe Jordanian critical care nurses' experiences of autonomy in their clinical practice. Design/methodology/approach A descriptive correlational design was applied using a self-reported cross-sectional survey. A total of 110 registered nurses who met the eligibility criteria participated in this study. The data were collected by a structured questionnaire. Findings A majority of critical care nurses were autonomous in their decision-making and participation in decisions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…The freedom to make patient care decisions and work independently is crucial as it reportedly allows full utilization of nurses’ knowledge and abilities (Budge et al., 2003; Duffield et al., 2009; Smith et al., 2006). Important elements of independence in work include the abilities to make independent decisions in the best interests of patients (Georgiou et al., 2017; Karanikola et al., 2014; Maharmeh, 2017; Stewart et al, 2004; Varjus et al., 2003), solve problems without orders, take nursing actions (Abdolmaleki et al., 2019; Berti et al., 2008; Georgiou et al., 2017; Karanikola et al., 2014; Stewart et al, 2004; Varjus et al., 2003) and organise unit operations (Varjus et al., 2003). Corresponding responsibility for one's own decisions and accountability for their consequences are also important (Attree, 2005; Cajulis & Fitzpatrick, 2007; Farrell et al., 2017; Garon et al., 2009; Georgiou et al., 2017; Karanikola et al., 2014; Skår, 2010; Stewart et al., 2004; Varjus et al., 2003; Wang et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The freedom to make patient care decisions and work independently is crucial as it reportedly allows full utilization of nurses’ knowledge and abilities (Budge et al., 2003; Duffield et al., 2009; Smith et al., 2006). Important elements of independence in work include the abilities to make independent decisions in the best interests of patients (Georgiou et al., 2017; Karanikola et al., 2014; Maharmeh, 2017; Stewart et al, 2004; Varjus et al., 2003), solve problems without orders, take nursing actions (Abdolmaleki et al., 2019; Berti et al., 2008; Georgiou et al., 2017; Karanikola et al., 2014; Stewart et al, 2004; Varjus et al., 2003) and organise unit operations (Varjus et al., 2003). Corresponding responsibility for one's own decisions and accountability for their consequences are also important (Attree, 2005; Cajulis & Fitzpatrick, 2007; Farrell et al., 2017; Garon et al., 2009; Georgiou et al., 2017; Karanikola et al., 2014; Skår, 2010; Stewart et al., 2004; Varjus et al., 2003; Wang et al., 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence from international studies have shown considerable levels of autonomy among nurses (Amini, Negarandeh, Ramezani‐Badr, Moosaeifard, & Fallah, ; Bahadori & Fitzpatrick, ; Iranmanesh, Razban, Nejad, & Ghazanfari, ; Maharmeh, ). A variety of individual and organizational factors have been identified to influence professional autonomy in nurses.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from international studies have shown considerable levels of autonomy among nurses (Amini, Negarandeh, Ramezani-Badr, Moosaeifard, & Fallah, 2015;Bahadori & Fitzpatrick, 2009;Iranmanesh, Razban, Nejad, & Ghazanfari, 2014;Maharmeh, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Critical care nurses' in KSA were found to be autonomous in decision-making and independent in their clinical practice (Maharmeh, 2017). Another study was conducted in KSA to review nurse managers actions to promote the autonomy of their nurses reported that the improvement of relations with other healthcare professionals and the enhancement of working life and culture were the main actions utilized by the nurse managers to improve the nurses perception of their autonomy (Mrayyan, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The five independent factors include five factors (organization culture and climate, the relationship and cooperation, facilities and adequate resources, compensation and rewards, and training and development). The dependent factor includes autonomy of work factor (Calvo et al, 2014;Conroy & Douglas Coatsworth, 2007;MacDonald, 2002;M Maharmeh, 2017;Maylone et al, 2011;Mrayyan, 2004).…”
Section: Conceptual Modelmentioning
confidence: 99%